THE IMPACT OF UNIVERSITY STUDENTS' PERSONAL VALUES AND MORAL COGNITION ON THEIR PERCEPTION OF SOCIAL RESPONSIBILITY - Hao Sun Hao Sun; Krittavit Bhumithavara (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
Against the backdrop of the in-depth development of globalization and informatization, where social responsibility has attracted widespread attention, and considering the significance of college students' qualities such as social responsibility—given that they are the future backbone of society—as well as the status of relevant empirical research in this field, this study takes full-time college students from Shenzhen University, South China Agricultural University, and Yanshan University as samples. It collects data through questionnaires and in-depth interviews, conducts empirical analysis using statistical tools, constructs a research framework of "personal values - moral cognition - social responsibility cognition", formulates hypotheses, and explores the relationships among the three. The study finds that various dimensions of personal values have a significant impact on idealism and are significantly correlated with relativism; idealism, relativism, and ethics all have a significant impact on the cognition of social responsibility, and under the influence of ethics, idealism and relativism have a significant impact on the cognition of social responsibility. Based on these findings, the study is of great significance and provides support for college students' self-awareness and the establishment of correct values; the design of college courses and moral education work; the cultivation of high-quality talents in society; and the realization of social harmony and sustainable development